2018
DOI: 10.7197/223.v40i37154.410205
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between lymphocyte / monocyte ratio and short-term mortality in acute ischemic stroke patients.

Abstract: The lymphocyte / monocyte ratio (LMR) obtained by dividing the number of lymphocytes by monocyte number is considered a new marker of inflammation. Recent studies have found an inverse relationship between LMR levels and 3-month functional recovery after acute ischemic stroke (AIS). Our aim in this study is to determine the role of LMR in the short-term mortality of AIS patients. Method: Our study is a single centered retrospective study. 508 patients with AIS, who presented to our clinic between January 2011 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…9,10 The pathophysiology of lymphocyte activity in post stroke is not characterized yet, and also the other subtypes of leukocytes, i.e neutrophils and monocytes. 10,11 It is stated that the role of lymphocytes in acute ischemic stroke is still controversial. Lymphocytes infiltrate the ischemic tissue and mediate the inflammatory response, where it may increase the level of antiinflammatory cytokines and suppress the production of proinflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 The pathophysiology of lymphocyte activity in post stroke is not characterized yet, and also the other subtypes of leukocytes, i.e neutrophils and monocytes. 10,11 It is stated that the role of lymphocytes in acute ischemic stroke is still controversial. Lymphocytes infiltrate the ischemic tissue and mediate the inflammatory response, where it may increase the level of antiinflammatory cytokines and suppress the production of proinflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that a low lymphocyte count is associated with poor clinical neurological outputs and plays a negative role in long-term functional recovery. 10,11 The National Institute of Health Stroke Scale (NIHSS) has been used in most studies on acute strokes to evaluate the neurological outputs. The NIHSS is a stroke-specific quantitative scale that examines the level of consciousness, language function, neglect, visual fields, eye movements, facial symmetry, motor strength, sensation, and coordination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation